Bilateral tonic-clonic seizures and status epilepticus in autoimmune encephalitis - M. Yu. Maximova; E. A. Golovneva; A. G. Broutian; E. O. Chekanova; M. N. Zakharova (Эпилепсия и пароксизмальные состояния, 2025)
Background. Epileptic seizures are involved in the diagnostic criteria for autoimmune encephalitis (AE). In this regard, timing of onset of focal-to-bilateral tonic-clonic seizure (BTCS) transition and status epilepticus (SE) in AE is understudied.Objective: to compare the timing of onset for focal-to-BTCS and SE during AE.Material and methods. Examination of patients with AE included collecting patient history, conducting blood and cerebrospinal fluid tests, magnetic resonance imaging, and long-term electroencephalographic video-monitoring. Out of 41 examined patients, 22 (54%) were diagnosed with “suspected AE” and 19 (46%) patients had “verified AE”. Focal-to-BTCS were noted in patient history of 36 (88%) subjects, including subsequent SE observed in 12 (29%) cases.Results. A single focal-to-BTCS/SE was the first AE symptom found in 8 (22%) patients, including 1 patient bearing antibodies against glutamate decarboxylase 65 (GAD65). In 8 (22%) cases, AE manifested with focal seizures, whereas focal-to-BTCS and/or SE developed later. This type of AE course was most commonly observed in patients with anti-GAD65 antibody-positive encephalitis (4 out of 9 cases). Focal-to-BTCS and SE developed only at disease onset and during exacerbations of the immune process in 5 (14%) patients, 2 of whom carried anti-myelin oligodendrocyte glycoprotein antibodies.Conclusion. Focal-to-BTCS and SE most often emerge at AE onset. Anti-GAD65 antibody-positive encephalitis is manifested by long-lasting drug-resistant epilepsy with late onset of focal-to-BTCS and SE. In case of anti-GAD65 antibody-positive AE, epileptic seizures occur only at disease onset.